Marriage Dispensation From the Perspective of Women's Protection - Patmanasari, Rike; Salma, Nida; Ahmad, Fayiz Syafiq; Kania, Dede (Peneliti.net, 2023)
A marriage dispensation is a request for court permission to allow individuals to marry when they don't meet the legal age requirements. This study aims to analyze Determination Number 206/Pdt.P/2023/PA.Badg, focusing on the judge's rationale in granting marriage dispensation cases. The study reveals that the judge's decision is primarily based on the applicants being underage. However, the legal basis employed appears discriminatory and neglects women's protection, as it relies on Law No.1 of 1974, Perma No. 5 of 2019, and the Compilation of Islamic Law. Notably, the judge does not consider the principles outlined in Law No.7 of 1984, pertaining to the Convention on the Elimination of All Forms of Discrimination Against Women. Employing a juridical-normative approach and relying on secondary data sources, this research sheds light on the complexities of marriage dispensation cases and their legal implications.